THE PHYSIOLOGICAL RESPONSE, TIME-MOTION CHARACTERISTICS AND REPRODUCIBILITY OF VARIOUS SPEED ENDURANCE DRILLS IN ELITE YOUTH SOCCER PLAYERS: SMALL SIDED GAMES VS GENERIC RUNNING. Issue 17 (24th October 2013) - Ade, J; Harley, J; Bradley, P
Abstract : The aim of the study was to quantify the physiological responses, time-motion characteristics and reproducibility of various speed endurance production (SEP) and speed endurance maintenance (SEM) drills. Twenty-one elite male youth soccer players completed four drills: (1) SEP 1 v 1 small sided game, (2) SEP running drill, (3) SEM 2 v 2 small sided game and (4) SEM running drill. The SEP drills consisted of eight bouts of 30 s with 120 s recovery (1:4 exercise to rest ratio) whilst SEM drills encompassed eight bouts of 60 s with 60 s recovery (1:1 exercise to rest ratio). Heart rate response, blood lactate concentration, rating of perceived exertion and time-motion characteristics were recorded for each drill. The SEP and SEM running drills elicited greater ( P <0.05) heart rate responses, blood lactate concentrations and subjective ratings of perceived exertion than the equivalent small sided games (ES: 1.1–1.4 & 1.0–3.2). Players covered less ( P <0.01) total distance, high-, very high-speed running and sprint distance in the SEP and SEM small sided game's compared to the equivalent running drills (ES: 6.0–22.1 & 3.0–18.4). Greater distances ( P <0.01) were covered in high and maximum acceleration/deceleration bands during the SEP and SEM small sided game's compared to the equivalent running drills (ES: 2.6–4.6 and 2.3–4.8). Small-moderate test-retest variability was observed for heart rate response (CV: 0.9–1.9%), ratings of perceived exertion (CV: 2.9–5.7%) and blood lactate concentration (CV: 9.9–14.4%); Moderate-large test-retest variability was observed for high-intensity running parameters (CV: >11.3%) and the majority of acceleration/deceleration distances (CV: >9.8%) for all small sided games and running drills. The data demonstrate the differential response of SEP and SEM training for taxing various energy systems and the superior acceleration/deceleration profiles of small sided games compared to generic running drills.